Trends and hotspots in targeted therapy resistance research for renal cell carcinoma: a bibliometric and visualization analysis - Ziqian Wang; Xiaodu Xie; Ze Wang; Peng Tang; Jian Chen; Jing Xu; Junying Zhang; Haiyang Xiao; Chongliang Zheng; Jun Jiang; Qiuli Liu; Weihua Lan (Discover Oncology)
Abstract Background Molecular targeted therapies have shown considerable efficacy in treating metastatic renal cell carcinoma (mRCC). However, many patients still experience tumor recurrence or metastasis due to drug resistance. Despite extensive research on resistance mechanisms, there is a lack of comprehensive bibliometric studies examining the overall characteristics of targeted therapy resistance in renal cell carcinoma. Materials and methods Publications on resistance to targeted therapy in renal cell carcinoma were identified from the Web of Science Core Collection (WoSCC) from June 2004 to November 2024. The English-language literature was analyzed using bibliometric tools, including VOSviewer and CiteSpace, to examine publication trends, active countries/regions, key authors, and institutions. Keyword analysis, co-citation mapping, and gene identification were conducted to uncover research trends and focal points. Results A total of 1081 publications were identified, with the United States, China, and Italy as the top contributing countries. Prominent institutions included the Cleveland Clinic, the Sloan Kettering Cancer Center, the MD Anderson Cancer Center, Fudan University, and Huazhong University of Science and Technology. Camillo Porta was a prolific author, and Brian I. Rini was among the most highly cited. The journal Cancers published the most papers in this field, and the Journal of Clinical Oncology was the most co-cited. Key research topics included the “tumor microenvironment” and “combination therapy”. A comprehensive analysis of publications related to "the tumor microenvironment" reveals that "renal cancer stem cells" and "epithelial-mesenchymal transition" have been identified as key terms strongly associated with therapeutic resistance mechanisms in targeted cancer treatments. In-depth analysis of the regulatory molecules and molecular mechanisms in the literature highlighted the roles of microRNA and the synergistic effects between anti-PD-L1/PD-1 and targeted drugs. Conclusions Bibliometric analysis of research on molecular targeted therapy resistance in renal cell carcinoma revealed a clear trajectory and rapidly increasing trend in this field. The impact of the tumor microenvironment, particularly the roles of renal cancer stem cells and epithelial-mesenchymal transition, has garnered significant attention. Additionally, the combination of anti-PD-L1/PD-1 and targeted drugs, as well as the involvement of miRNA, have emerged as key areas of focus. As understanding of this field deepens, future research is expected to uncover novel therapeutic targets and more effectively overcome the challenges of targeted therapy resistance in renal cell carcinoma, ultimately improving patient outcomes.